2012
DOI: 10.1603/an11185
|View full text |Cite
|
Sign up to set email alerts
|

Early Leaf Abscission Has Little Effect on Larval Mortality of Ectoedemia cerviparadisicola (Lepidoptera, Nepticulidae) Associated with Quercus gilva

Abstract: There has been an argument as to whether early leaf abscission substantially affects larval mortality of leafminers because of leaf senescence. Recently, a study reported that leaf abscission considerably increased the mortality of a leafminer (Ectoedemia cerviparadisicola Sato, sp. nov.) associated with Quercus gilva (Blume) in Nara Park, central Japan, where sika deer (Cervus nippon (Temminck)) have been protected for 1,200 yr, because deer consumed many abscised leaves containing living larvae. The study, h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…Over the following two decades, various authors continued investigations of the Nepticulidae in Japan (Kumata & Nakatani 1995;van Nieukerken & Kuroko 2005;Hirano 2010;Shinozaki et al 2012), also Korea (Lee & Byun 2007), China (van Nieukerken & Liu 2000), and the Russian Far East (Puplesis & Diškus 2003). Male genitalia of the type material of the nepticulid species described from Primorskiy Kray (Russian Far east) were re-androconia; costal margin yellowish cream (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Over the following two decades, various authors continued investigations of the Nepticulidae in Japan (Kumata & Nakatani 1995;van Nieukerken & Kuroko 2005;Hirano 2010;Shinozaki et al 2012), also Korea (Lee & Byun 2007), China (van Nieukerken & Liu 2000), and the Russian Far East (Puplesis & Diškus 2003). Male genitalia of the type material of the nepticulid species described from Primorskiy Kray (Russian Far east) were re-androconia; costal margin yellowish cream (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…In Inayama Forest, many mines in early abscised leaves were filled with rainwater on rainy days, implying that some of the beetles in the abscised leaves drowned in rainwater. For example, when leaves drop early, leaf miners may be exposed to ground-feeding predators, such as ants and carabid beetles (Waddell et al, 2001;Oishi & Sato, 2007), and to mammalian herbivores that consume leaves containing leaf miners on the ground (Yamazaki & Sugiura, 2008), although the effect may be limited (Shinozaki et al, 2012). Temperature was not selected as a significant variable affecting the adult beetle population (Table 1).…”
Section: Meanmentioning
confidence: 99%
“…Several reports have shown that early leaf abscission negatively affects miner survivorship, albeit indirectly. For example, when leaves drop early, leaf miners may be exposed to ground-feeding predators, such as ants and carabid beetles (Waddell et al, 2001;Oishi & Sato, 2007), and to mammalian herbivores that consume leaves containing leaf miners on the ground (Yamazaki & Sugiura, 2008), although the effect may be limited (Shinozaki et al, 2012). Kahn and Cornell (1989) stated that the timing of leaf abscission in relation to the life cycle of herbivorous insects, and in relation to natural enemy attacks, determines the influence of abscission on herbivore demographics.…”
Section: Meanmentioning
confidence: 99%
“…Second, leaf miners could make leaves fall year-round and return the nutrients back to the tree in a more even way (Owen, 1978). Premature leaf abscission is positively correlated with the densities of the mines (Shinozaki et al, 2012). Infested cranberry leaves by Coptodisca negligens, those with two mines drop earlier than those with only one mine (Maier, 1989).…”
Section: Impacts On Plant Growth and Productionmentioning
confidence: 99%
“…For example, <40% of mined leaves drop early (Kahn & Cornell, 1983); less than 3% of leaf miner larvae in dropped leaves suffer mortality (Pritchard & James, 1984a;Oishi & Sato, 2007;Gripenberg & Roslin, 2008;Shinozaki et al, 2012); and photosynthesis is not reduced enough to severely damage the host plant (Parrella et al, 1985;Martens & Trumble, 1987;Raimondo et al, 2003;Bueno et al, 2007). Moreover, early leaf abscission has no influence on holly leaf miner survivorship (Kahn & Cornell, 1989).…”
Section: Impacts On Plant Growth and Productionmentioning
confidence: 99%